On the origins of food loss. Issue 2 (4th March 2021) - Delgado, Luciana; Schuster, Monica; Torero, Maximo
Abstract: In this paper, we try to understand what the main causes of food losses (FLs) are. Our results show that producers' education and experience and the number of years in which a producer has been involved in the production of a specific crop are significantly correlated with reduction in FL. Unfavorable climatic conditions, pests, and diseases, as well as limited knowledge and access to equipment, credit, and markets, are also challenges to increasing production of higher quality and therefore reasons for FL. Policies to reduce and prevent FL need to be targeted to specific commodities and contexts. JEL CLASSIFICATION: Q13; Q18; Q58